DEVELOPMENT STAGE, AGEING AND NATURAL MORTALITY OF ANCHOVY EGGS (Encrasicholina SPECIES) FROM BACAN - Retno Andamari; Andriko N. Susanto; David A. Milton (Research Center for Fisheries, 1998)
ln order to study the possible application of the Daily Egg Production Method (DEPM) for estimating anchovy (Encrasicholina spp.) biomass at Bacan. Maluku, we collected a large series of plankton samples.